Black paintings in the late Yocavil ceramics (11th–17th centuries): Applying micro X-ray diffraction to the study of archaeological potteries in Northwest Argentina - (:unkn) unknown (Wiley Blackwell Publishing, Inc, 2024)
The black pigments used in Late Period (11th–17th centuries) painted pottery in the Yocavil Valley were characterized. Changes and continuities in the composition of this material over an extended span were evaluated. A regional sample of 47 potsherds from the Loma Rica, San José, and Santa María styles was collected, and for the first time micro wide-angle X-ray scattering was used in these ceramic styles. The results indicate the simultaneous presence of iron oxides (hematite) and solid solutions of manganese and iron oxides (jacobsite–magnetite). Besides, the paints were prepared by mixing the pigments with clay-based binding materials.

Fuertes, M. C., Palamarczuk, V., Huck-Iriart, C., & Lamas, D. G. (2024). Black paintings in the late Yocavil ceramics (11th–17th centuries): Applying micro X-ray diffraction to the study of archaeological potteries in Northwest Argentina. Archaeometry, 1-20.
Fil: Fuertes, María Cecilia. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina
Fil: Fuertes, María Cecilia. Comisión Nacional de Energía Atómica. Centro Atómico Constituyentes. Gerencia Química e Instituto de Nanociencia y Nanotecnología; Argentina
Fil: Palamarczuk, Valeria. Universidad de Buenos Aires. Facultad de Filosofía y Letras; Argentina
Fil: Palamarczuk, Valeria. Consejo Nacional de Investigaciones Científicas y Técnicas. Universidad de Buenos Aires. Instituto de las Culturas; Argentina
Keywords: Argentine Northwest; Black pigment; EDS; Loma Rica pottery; Micro X-ray diffraction; San José pottery; Santa María pottery; WAXS